Stars In The Perspective of Al-Qur'an - Santi Marhamah; Firly Hidayanti; Ida Yunengsih; Leli Nur Hapipah; Nadila Khoerunnisa; Agus Hidayat (Journal of Ulumul Qur'an and Tafsir Studies, 2022)
Abstract [Stars in the Perspective of the Al-Quran]Human observation of this nature is to prove the signs of Allah's power and greatness through His verses, and to increase the level of faith and piety of a servant to Allah by observing the signs of His creation. The star is one of the proofs of God's power and greatness that humans should take lessons from, the star is a means to know God rationally, and serves to inspire reason. tars have an important role in human life. A star is one of the celestial bodies that have and emits light, generally seen at night. For example, stars decorate the sky, as a signpost. Because it is so urgent that even Allah uses the stars as an instrument of oath. Stars are God's creations that store a lot of wisdom behind His existence. As for in the Koran the word star is referred to by 5 terms, namely al-Najm, al-Buruj, al-Kaukab, Al-Toriq and al-Khunnas. These have their respective classifications and differences. Of course, these terms are not born just like that, but they have their own meaning from Allah. Keywords Stars — al-quran — interpretation